Early Cryoprecipitate Transfusion Versus Standard Care in Severe Postpartum Haemorrhage: A Pilot Cluster-randomized Trial. Issue 4 (21st December 2022) - Green, L.; Daru, J.; Gonzalez Carreras, F.J.; Lanz, D.; Pardo, M.C.; Perez, T.; Philip, S.; Tanqueray, T.; Khan, K.S.; ,
Abstract : ( Anaesthesia . 2022;77:175–184) Fibrinogen levels play a key role in maintaining homeostasis during postpartum hemorrhage (PPH). Fibrinogen levels <2 g/L is significantly associated with adverse outcomes. Fibrinogen substitution effectively improves outcomes in severe PPH. However, the only studies evaluating early fibrinogen use describe the fibrinogen concentrate utilization, although cryoprecipitate is the more commonly used product. This study assessed the feasibility of early cryoprecipitate administration during PPH and other aspects needed to conduct future large trials to evaluate early cryoprecipitate use in PPH.